From ‘either/or’ to ‘both/and’:: Some thoughts on graffiti and street art conservation, curatorial practices and the handling of cultural heritage - Glaser, Katja (Street Art & Urban Creativity, 2017)
The institutionalization of street art and graffiti has been discussed a thousand times. My article takes the next step and asks: Are we not simply in charge of reevaluating the ‘interventions’ happening outdoors, be they commissioned or not, and integrating them into (fine art) shows, exhibitions and museum collections – with no attempt to plexiglass? The long-term perspective might be an equal treatment of commissioned and uncommissioned artworks, as well as the appreciation and self-confident exposition of their direct and unambiguous linkage. This article includes interviews with Pietro Rivasi (Italy) and Robert Kaltenhäuser (Germany) and refers to the ‘BLU controversy’ in Bologna, Italy. The text was written with regard to an exhibition that took place in Herne, Germany, where I contributed as a curatorial and scientific assistant.